Association of platelet-to-high-density lipoprotein cholesterol ratio and its cumulative exposure with cardiovascular disease risk: a prospective cohort study in Chinese population - Luo, Honglian; Li, Gang; Chen, Yan; Shen, Yun; Shen, Wei (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aimed to investigate the association of platelet-to-high-density lipoprotein cholesterol ratio (PHR) and its cumulative exposure with cardiovascular disease (CVD) risk.MethodsThe investigation utilized data from the China Health and Retirement Longitudinal Study (CHARLS). Platelet-to-high-density lipoprotein cholesterol ratio was calculated as platelet count (×10⁹/L)/high-density lipoprotein cholesterol (mmol/L), and a cumulative platelet-to-high-density lipoprotein cholesterol ratio (Cumulative PHR) was derived for longitudinal assessment. Multivariable logistic regression models were used to evaluate the association between PHR, cumulative PHR, and CVD risk across three models with increasing adjustments for confounders. Restricted cubic splines (RCS) regressions were utilized to examine if there were non-linear relationships. Subgroup analyses were conducted to enhance the reliability of the study findings. Furthermore, predictive performance was assessed using concordance index (C-index), net reclassification improvement (NRI), and integrated discrimination improvement (IDI).ResultsA total of 7,063 participants aged 45 and older were included, of whom 1,433 (20.29%) experienced a cardiovascular disease. Participants with CVD had higher PHR (167.93 vs. 156.84, P < 0.001) and Log PHR (5.12 vs. 5.06, P < 0.001) values compared to non-CVD participants. Multivariable logistic regression revealed that Log PHR was independently associated with CVD risk [Odds ratio (OR) per-unit: 1.30, 95% confidence interval (CI): 1.13–1.49, P < 0.001; OR per- standard deviation (SD): 1.13, 95% CI: 1.06–1.21, P < 0.001]. Log cumulative PHR showed similar associations (OR per-unit: 1.34, 95% CI: 1.05–1.71, P = 0.02). Participants in the highest quartile of Log PHR had a nearly 1.32-fold higher risk of CVD compared to the lowest quartile (OR: 1.32, 95% CI: 1.10–1.57, P = 0.002). Addition of Log PHR and Log cumulative PHR slightly improved predictive performance metrics of baseline model.ConclusionBoth Log PHR and Log cumulative PHR are independently associated with increased CVD risk and slightly improved the predictive performance of the baseline risk model. Future research should focus on its clinical implementation and integration into existing risk assessment frameworks.